Controlled entropy in tetra-hybrid nono-fluid helmholtz electroosmotic with motile germs via complex peristaltic pumping - Mohamed Boujelbene; Mohamed Ben Ammar; Nouman Ijaz; Ashraf M.M. Abdelbacki; Ahmed Zeeshan; Najma Saleem; Nidhal Ben Khedher (Case Studies in Thermal Engineering)
Motile microorganisms, such as bacteria, can be engineered to transport medications directly to certain organs, such as cancer, tumors, enhancing drug efficacy and minimizing systemic side effects. These microorganisms can also be programmed to target and eliminate harmful bacteria, offering a novel approach to infection control. In parallel, functionalized nanomaterials show significant promise for precise manipulation of biological fluids. This focused approach improves drug efficacy while reducing systemic negative effects. Also, motile bacteria can be engineered to target and remove dangerous bacteria, providing a fresh approach to infection control. Nanomaterials with various functions show prodigious potential for precise operation of biological fluids. Tetra-hybrid nano-particles exhibit special electrical, optical, and thermal properties. They are composed of gold, silver, alumina, and titania. The streaming flow phenomena that result from the interactions of these nanocomposites with non-Newtonian biofluids, such as blood, can be studied using computational modeling. Considerations are made for forces such as non-Newtonian rheology, localized laser irradiation, and magnetohydrodynamics. Complex cellular trapping patterns are captured by predictions for temperature, velocity, and nanoparticle concentration profiles. Biocompatible multimodal nano-assemblies under magnetic actuation and thermos-plasmonic effects are used to exhibit precision biofluid control. To optimize, engineering parameters are visually analyzed. The unique features of tetra-hybrid nanoparticles, paired with motile microorganisms and non-Newtonian biofluid dynamics, allow for more precise therapeutic techniques, such as targeted medication administration and hyperthermia cancer treatment. By visualizing key engineering parameters, these findings highlight the potential for improved therapeutic strategies, such as targeted drug delivery and hyperthermia-based cancer treatments, enabled by the integration of tetra-hybrid nanoparticles and motile microorganisms in complex biofluid environments.